Effects of urbanization on animal communities (Zoological Records and Reviews, 2024)
Urbanization generates a distinctive suite of environmental filters -- elevated temperatures, impervious surfaces, artificiallight at night (ALAN), noise pollution, and chemical contamination -- that systematically restructure animal communitiesalong urban-rural gradients. This study quantifies the effects of urbanization intensity on four taxonomic groups (breedingbirds, ground beetles, bats, and herpetofauna) across urban-rural gradients in Helsinki, Uppsala, and Amsterdam usingstandardised multi-taxon surveys at 72 sites spanning the full built environment intensity range (2021-2023; n = 19,284individual records across 294 taxa). Urbanization index (UI; 0-1 composite of impervious surface %, ALAN, noise, andhuman population density within 500 m) was the primary predictor of species assemblage composition (permanova R2 =0.48, p < 0.001). Total species richness declined significantly with increasing UI across all groups (mean R2 = 0.54; all p< 0.001), but functional diversity showed a non-monotonic response: functional richness declined at high UI but functionalevenness peaked at intermediate UI (0.4-0.6) where urban generalist and specialist species co-occur. Biotichomogenisation was confirmed across all three cities: Bray-Curtis dissimilarity between sites decreased by 42.4 +- 6.8%from rural to urban cores. ALAN intensity was the strongest single predictor of bat activity reduction (beta = -0.72 +- 0.10,p < 0.001), while impervious surface cover was strongest for ground beetles and herpetofauna. Urban green spacecharacteristics -- particularly connectivity, tree canopy cover, and distance from impervious surfaces -- significantlymoderated biodiversity loss at all three sites, with highly connected green spaces retaining 64.8% of rural referencerichness versus 28.4% in isolated urban parks. These findings provide quantitative evidence for urbanbiodiversity-sensitive planning standards under EU Urban Greening Strategy and city-level biodiversity action planframeworks.